Flood analysis and non-structural approach for flood protection in Sg. Kelantan - Nor Azlan Shah, Nurul Fatihah; Abd Hakim, Nur Wajihah; Salleh, Md Noor; Ali, Maisarah; Ayob, Mohd Fairullazi; Sekaran, Thayalam; Ismail, Mohd Azmi; Mat Amin, Mohd Zaki (IOP Publishing Ltd, 2022)
Flooding is categorized as a natural disaster that occurs due to various climatic and geophysical factors. Malaysia is a lucky country as it experiences a tropical climate and generally protected from extreme drought. However, the states located along the east coast of the Peninsular Malaysia such as Kelantan, Terengganu, and Pahang always experienced a heavy flood, especially during the monsoon season due to high intensity of rainfall. The objectives of this paper were to simulate Flood Hydrographs for Various Storm Duration by using Hydrologic Engineering Centre-Hydrologic Modelling System (HEC-HMS), to investigate the location of floodplain at the catchment area of Sg. Kelantan by using River Analysis System (HEC-RAS), to identify the non-structural approach that can reduce the rate of flood based on its topography. By using HEC-HMS and HEC-RAS software, the peak discharge from each rainfall stations for different average recurrence interval (ARI) were calculated. Various non-strctural measures to reduce the impacts of flood are discussed.